2024
DOI: 10.1186/s12977-024-00634-1
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine receptor CCR5: multi-faceted hook for HIV-1

Natacha Faivre,
Christel Verollet,
Fabrice Dumas

Abstract: Chemokines are cytokines whose primary role is cellular activation and stimulation of leukocyte migration. They perform their various functions by interacting with G protein-coupled cell surface receptors (GPCRs) and are involved in the regulation of many biological processes such as apoptosis, proliferation, angiogenesis, hematopoiesis or organogenesis. They contribute to the maintenance of the homeostasis of lymphocytes and coordinate the function of the immune system. However, chemokines and their receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 234 publications
(243 reference statements)
0
0
0
Order By: Relevance
“…A popular and promising tool includes gene editing systems such as the CRISPR/Cas9 system [ 82 ]. A promising target is the CCR5 co-receptor, an entry port for the HI Virus into the CD4+ Lymphocyte [ 83 ]. Clinical trials for gene therapies using CCR5 as a target have shown promising results, with some patients achieving long-term viral suppression [ 42 ].…”
Section: Gene Therapy Against Hivmentioning
confidence: 99%
“…A popular and promising tool includes gene editing systems such as the CRISPR/Cas9 system [ 82 ]. A promising target is the CCR5 co-receptor, an entry port for the HI Virus into the CD4+ Lymphocyte [ 83 ]. Clinical trials for gene therapies using CCR5 as a target have shown promising results, with some patients achieving long-term viral suppression [ 42 ].…”
Section: Gene Therapy Against Hivmentioning
confidence: 99%